Pregabalin dependence: a case report - Oğuz, Gülay; Güven, F. Mükerrem; Batmaz, Sedat (Journal of Dependence, 2015)
Pregabalin is a new generation antiepileptic drug that exerts its effects by decreasing the release of neurotransmitters, such as glutamate, noradrenaline, and substance P. Pregabalin is a gamma-aminobutyricacid (GABA) analogue utilized in the treatment of neuropathic pain and generalized anxiety disorder, in addition to epilepsy. There have been studies conducted in recent years demonstrating the effectiveness of Pre-gabalin in the treatment of benzodiazepine and alcohol dependence. However, there have also been cases in which pregabalin dependence developed. As such, pregaba-lin should be used with caution. This article presents a case report of a 27-year-old man who started on pregabalin in order to discontinue synthetic marijuana (Jamaica) use, then abused it and exhibited withdrawal symptoms when not using it. The patient had been taking 2100 mg/day of pregabalin, and stated that he experienced withdrawal symptoms including irritability, shaking, heartburn, inertia, depression, and an inability to work when he hadn’t taken the medicine. His daily dose of pregaba-lin was decreased according to a provided chart and he was started on paroxetine at 20 mg/day, and quetiapine XR at 50 mg/ day. Following this intervention, the patient managed to quit pregabalin within 60 days.